Are Continued Efforts to Reduce Radiation Exposures from X-Rays Warranted? - Paul A. Oakley; Deed E. Harrison (SAGE Publishing, 2021)
There are pressures to avoid use of radiological imaging throughout all healthcare due to the notion that all radiation is carcinogenic. This perception stems from the long-standing use of the linear no-threshold (LNT) assumption of risk associated with radiation exposures. This societal perception has led to relentless efforts to avoid and reduce radiation exposures to patients at great costs. Many radiation reduction campaigns have been launched to dissuade doctors from using radiation imaging. Lower-dose imaging techniques and practices are being advocated. Alternate imaging procedures are encouraged. Are these efforts warranted? Based on recent evidence, LNT ideology is shown to be defunct for risk assessment at low-dose exposure ranges which includes X-rays and CT scans. In fact, the best evidence that was once used to support LNT ideology, including the Life Span Study data, now indicates thresholds for cancer induction are high; therefore, low-dose X-rays cannot cause harm. Current practices are safe as exposures currently encountered are orders of magnitude below threshold levels shown to be harmful. As long as imaging is medically warranted, it is shown that efforts to reduce exposures that are within background radiation levels and that are also shown to enhance health by upregulating natural adaptive protection systems are definitively wasted resources.